Distribution system reconfiguration for service restoration - Ng, Wilson Jun Wei (Nanyang Technological University, 2020)
The readiness of power supply cannot be compromised in every second worldwide. This boils down to the design of electrical circuit connection as well as the efficiency of power restoration methods. The latter will be of utmost importance to countries in which natural disasters are inevitable or when dealing with all sorts of power disruptions. With this, the objective of this project will therefore be an extension of past research with great emphasis placed on reliability-based restoration of microgrids as the main strategic method to ensure power restoration within seconds. The schematics of main circuit connection, function of microgrids and mathematical modelling equations of constraint will need to be studied before a simulation will be developed using a software named python. At the end, challenges and future work that can be done will be discussed and thus making the study of power system resilience in power restoration to be endless and crucial.